Chaotic signatures of photoconductive Cu2ZnSnS4 nanostructures explored by Lorenz attractors - M A Hernández-Acosta; M Trejo-Valdez; J H Castro-Chacón; C R Torres-San Miguel; H Martínez-Gutiérrez; C Torres-Torres (New Journal of Physics, 2018)
Photoconductive and third-order nonlinear optical properties exhibited by Cu _2 ZnSnS _4 nanostructures are presented. The samples were synthetized in thin film form by a spray pyrolysis processing route. Distinctions in the photoconductive behavior throughout the samples were clearly noted by modulating their optoelectronic response dependent on electrical frequency. Vectorial two-wave mixing experiments were carried out at a 532 nm wavelength provided by a Nd:YAG laser system to study the optical nonlinearities in the samples. An induced transparency effect was observed during nanosecond single-beam experiments in the nanostructures reported. Quantum and thermal processes were considered to be the main physical mechanism responsible for the photo-electrical phenomena and nonlinear refraction in the nanostructures. Potential applications for developing nanophotonic and nanoelectronic instrumentation systems can be contemplated.